Serum IL-1, Pyroptosis and Intracranial Aneurysm Wall Enhancement: Analysis Integrating Radiology, Serum Cytokines and Histology - Liu, Qingyuan; Zhang, Yisen; Zhu, Chengcheng; Liu, Weiqi; Ma, Xuesheng; Chen, Jingang; Mo, Shaohua; Dong, Linggen; Wang, Nuochuan; Wu, Jun; Liu, Peng; He, Hongwei; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background and Purpose Aneurysm wall enhancement (AWE) is correlated with the rupture and growth risk of unruptured intracranial aneurysms (UIAs). Pyroptosis is a proinflammation mode of lytic cell death, mediated by pyroptosis-related proteins, i.e., gasdermin D and interleukin 1 β (IL-1β). Integrating serum cytokines and histology, this study aimed to investigate the correlation between AWE and pyroptosis in UIAs. Methods UIA patients receiving microsurgical clipping were prospectively enrolled from January 2017 and June 2020. UIA samples were collected, as well as the corresponding blood samples. In this study, high-resolution magnetic resonance was employed to identify the AWE. The serum 46-cytokines examination and the histological analysis were conducted to determine pyroptosis, CD68 and MMP2. The IL-1 ra/beta ratio was determined by complying with the serum IL-1β and IL-1.ra. A comparison was drawn in the differences between UIAs with and without AWE. Lastly, the correlation between inflammation in UIA samples and serums was investigated. Results This study included 34 UIA patients. The serum proinflammatory cytokines [IL-1β (P < 0.001) and TNF-α (P < 0.001)] were up-regulated, and serum anti-inflammatory cytokine (IL-1.ra, P = 0.042) were down-regulated in patients with AWE UIAs. The patients with AWE UIAs achieved a higher IL-1.ra/beta ratio (P < 0.001). The multivariate logistic analysis demonstrated IL-1β [odds ratio (OR), 1.15; 95% confidence interval (CI), 1.02–1.30; P = 0.028] and IL-1.ra (OR, 0.998; 95% CI, 0.997–1.000; P = 0.017) as the risk factors correlated with the AWE. IL-1.ra/beta ratio achieved the highest predictive accuracy [area under the curve (AUC), 0.96] for AWE, followed by IL-1.ra (AUC, 0.90), IL-1β (AUC, 0.88) and TNF-α (AUC, 0.85). As compared with the UIAs without AWE, the AWE UIAs were manifested as a severer wall remodeling, with higher relative levels of pyroptosis-related proteins, CD68 and MMP2. The serum IL-1β, IL-1.ra and IL-1.ra/beta ratio had a positive correlation with the relative levels of pyroptosis-related proteins, CD68 and MMP2 in UIA tissues. Conclusion The serum IL-1β and IL-1.ra were correlated with the AWE. More pyroptosis-related proteins were identified in UIAs with AWE. The serum IL-1β and IL-1.ra were correlated with the pyroptosis-related proteins in aneurysm tissues.